Ruminal acidosis - Millen, Danilo Domingues [UNESP]; Pacheco, Rodrigo Dias Lauritano; Da Silva Cabral, Luciano; Cursino, Lia Locatelli [UNESP]; Watanabe, Daniel Hideki Mariano [UNESP]; Rigueiro, André Luiz Nagatani [UNESP] (Springer Nature, 2016)
Ruminants are herbivores that have developed themselves in biosphere in order to consume forages (grasses and legumes), which are characterized by the high content of cell wall; although there are variations related to ruminants’ species regarding their capacity to select plants with smaller contents of these compounds (Van Soest et al. 1991). The intake of this type of diet keeps the reticulum-rumen (main digestive compartment of these animals) with a set of physical and chemical characteristics that are considered appropriate to maintain the animal’s ruminal microbiota and health. However, due to the need to increase (beef and milk) production, ruminants have been subjected to different diet conditions, from those that they evolved consuming, which may contain large amounts of carbohydrates that quickly ferment in the rumen and cause a series of digestive and metabolic disorders like ruminal and metabolic acidosis, rumenitis, bloat, liver abscesses and laminitis (González et al. 2012).